Introduction of Currency to Stimulate Numeracy Skills in Kindergarten - Hermawan, Toto; Rahayu, Suprati Hardi; Imroatun, Imroatun; Umayah, Umayah; Fitriah, Diamah; Rojifah, Eva (UIN Sultan Maulana Hasanudin Banten, 2025)
One part of mathematics that is widely felt to be beneficial in everyone's daily life is numeracy, especially the concept of numbers. Numbers are also in currency that needs to be understood early on by all parties. This qualitative study aims to describe how children who study in kindergarten get an introduction to Indonesian currency and explore more deeply about the process of stimulating numeracy skills, especially those running in PAUD BKB Kemas Nuri, Ciruas District, Serang Regency. the introduction of currency value in stimulating children's counting skills that is carried out is still complementary. This can be seen from the introduction activities, namely saving, playing the role of buying and selling or giving alms. In this position, the formation of certain characters is prioritized over children's counting skills. So an introduction with a clear focus can be planned for children.